Data Communication through Distribution Network for Smart Grid Applications - El Haj, Youssef (2014)
A Master of Science thesis in Electrical Engineering by Youssef El Haj entitled, "Data Communication through Distribution Network for Smart Grid Applications," submitted in May 2014. Thesis advisor is Dr. Lutfi Albasha and thesis co-advisor is Dr. Ayman Hassan El-Hag. Available are both soft and hard copies of the thesis.